Relevance of implementation, application and multimedia technologies’ development in tertiary education - E. A. Tatarinova (Вестник университета, 2023)
The article deals with the advantages and prospects of implementing multimedia technologies necessary for the development of the traditional, already familiar model of education and bringing it to a new level of innovation. The introduction of multimedia technology in educational processes is one of the key moments of education informatization. Nowadays multimedia technologies are one of the most dynamically developing and promising areas of information services. The effectiveness of multimedia methods use directly depends on the professional competence of teachers and the ability to teach graduates the necessary profession skills, which meet modern requirements. The use of e-learning methods opens up opportunities for further implementation of new ideas and trends in the development of tertiary education in Russia. The technological process does not stand still and advanced IT technologies have become an integral part of modern education.